Ecophysiological constraints of Aster tripolium under extreme thermal events impacts: Merging biophysical, biochemical and genetic insights - Duarte, Bernardo (2020)
Cold and heat waves are phenomenon that occurs in higher frequency and intensity due to global climate changes. Commonly cultivated crop species are crucially affected by extreme weather events, and therefore alternative crops - such as halophytes - gain in agricultural interest. While halophytes are potentially able to cope with temperature extremes on the long term exposure, effects of temporary events such as cold and heat waves are not yet described. In order to unveil the effects of these altered thermal environments, Aster tripolium plants were subjected to cold (9/5 °C) and heat (42/38 °C) waves regimes during 3 days and its photochemical and biochemical traits evaluated. In the potential cash crop A. tripolium cold waves induced the gene expression of dehydrins in order to counteract desiccation and thus to prevent oxidative stress. Regulatory proteins on the RNA maturation level (Maturase K) were highly expressed. Heat stress induced the gene expression of the cystein protease gene; most likely to degrade misfolded proteins temporary. Both thermal treatments decreased the photosynthetic efficiency and capacity, driven by a loss in the connectivity between PSII antennae. Nevertheless the light absorption capacity was unaffected due to an increased RC closure net rate. Cold wave-treated individuals showed a decrease in the carotenoid pigmentation, except auroxanthin. In cold wave treated individuals the overall peroxidase activity was significantly increased. Data suggest that exposure to both, cold and heat wave treatment decreased the ecophysiological capacity of A. tripolium.